Technique of implantation and feasibility, "in vitro" in aortas porcinas, of anastomose vascular end-terminal (Research, Society and Development, 2021)
The aim of this study was to demonstrate the feasibility, "in vitro", in porcin aortas, of end-to-end vascular anastomosis, with UnitaryAnastomotic Device (UAD®), titanium and describe the implant technique. This is an experimental, "in vitro" study carried out at the Experimental Surgery Center of the Federal University of Pernambuco. The external and internal aspects of vascular anastomoses presented: Absence of elbow or bulging in the anastomoses and maintenance of the longitudinal axis of the vessel, as well as macroscopic integrity of the vascular endothelium, regular edges, absence of suture at the site of the anastomoses, absence of irregularities and roughness. Based on this experimental study, it can be concluded that the terminal-terminal Anastomoses "in vitro", with porcin aortas and titanium prosthesis - UAD®- Unitary Anastomotic Device: Did not present external deformations at pressure of up to 420 mmHg; Externally maintained regularity, without cotoves, without bulging, without deformities in the longitudinal plane of the aorta, between the proximal and distal cables to the anastomosis;  Internally, all anastomoses maintained the circular shape, regular lips, intact endothelium macroscopically, complete absence of suture threads, absence of roughness and lacerations and all anastomoses resisted 420mmHg, without leakage.